Efficacy of Duplex Ultrasound for the Evaluation of Carotid Artery Stenosis in Comparison to Digital Subtraction Angiogram (Bangladesh Journal of Neuroscience, 2026)
Background: Carotid artery stenosis is one of the important causes of ischemic stroke. This is responsible for 10% of all ischemic stroke events. This may be diagnosed as duplex Ultrasound (USD) and DSA both of which have some advantages and disadvantages. Objective: The aim of this study was to assess efficacy of duplex USD for the evaluation of extra-cranial carotid artery stenosis among patients of ischemic stroke and Transient Ischemic Attack (TIA) in comparison to (DSA).Materials and Methods: This observational cross sectional study was conducted among 50 patients in the Dept of Neurology in BSMMU and National Institute of Nuclear Medicine and Allied Sciences (NINMAS), BSMMU campus, Dhaka. Duplex USD of neck vessels of all cases were performed and reported by selected specialist of (NINMAS). Patients were also referred to cathlab of BSMMU for DSA performed by two interventional neurologists blinded of USD finding. Diagnostic performance test was done between duplex USD and DSA at e” 50%, e” 70%, 100% cut off point of stenosis of right internal carotid artery (RICA) and left internal carotid artery (LICA).Results: This study showed that in RICA for e” 50%, e” 70% and 100% stenosis sensitivity were 82%, 89% and 93% respectively. In LICA for e” 50%, e” 70% and 100% stenosis sensitivity were 82%, 91%, 95% respectively. The study revealed that in RICA for e” 50%, e” 70% and 100% stenosis specificity were 86%, 83% and 80% respectively. In LICA for e” 50%, e” 70% and 100% stenosis specificity were 85.2%, 93%, 86% respectively. The present study also showed that in RICA for e” 50%, e” 70% and 100% stenosis efficacy were 84%, 88% and 92% respectively. In LICA for 70% and 100% stenosis efficacy were 88%, 92%, 94% respectively.Conclusion: In present study the sensitivity, specificity and efficacy of duplex USD is high at different degree of cut off point of carotid stenosis keeping DSA as standard. Results of this study are also matched with other similar type of studies done abroad